2016
DOI: 10.1007/s12471-016-0932-5
|View full text |Cite
|
Sign up to set email alerts
|

Early experience with the Venus p‑valve for percutaneous pulmonary valve implantation in native outflow tract

Abstract: IntroductionThe Venus p‑valve (MedTech, Shanghai, China) is a self-expanding percutaneous heart valve designed to be implanted in a native patched right ventricle outflow tract. The worldwide clinical experience with this valve is just beginning and the results have so far been encouraging. We present our initial early experience implanting the Venus p‑valve in the native right ventricle outflow tract of patients with Tetralogy of Fallot repaired with a transannular patch.MethodsIn 10 selected patients a proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
53
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 13 publications
0
53
0
2
Order By: Relevance
“…In 2017, Garay et al reported successful implantation of the Venus P-valve in 10 patients (seven female) [25]. The patients' mean age was 32 years and mean weight was 59.6 kg.…”
Section: Clinical Experiencementioning
confidence: 99%
“…In 2017, Garay et al reported successful implantation of the Venus P-valve in 10 patients (seven female) [25]. The patients' mean age was 32 years and mean weight was 59.6 kg.…”
Section: Clinical Experiencementioning
confidence: 99%
“…In addition, a drop (from 125 mm Hg to 90 mm Hg) of the aortic arterial pressure was observed during test balloon occlusion of the Gore-Tex tube indicating that the blood flow through native RVOT was not sufficient enough to maintain by itself a normal cardiac The valve implantation was performed under general anesthesia using the previously described technique. [2][3][4] Based on the angiographic measurements and the anatomic characteristics of the RVOT, a 36 mm diameter and 35 mm length flared Venus P-valve was successfully implanted from the RVOT to MPA bifurcation through a 24 F delivery system. (Figure 1 A,B,C,D).…”
Section: Introductionmentioning
confidence: 99%
“…However, only < 20% of patients following tetralogy Fallot repair are candidates for these two valves as they cannot be used in large patched right ventricular outflow tracts (RVOTs) [1]. The Venus P-valve (Venus Medtech, Shanghai, China) is a new self-expanding tri-leaflet porcine pericardial tissue percutaneous pulmonary valve designed specifically for implantation in large (up to 32 mm diameters) native RVOT [2][3][4]. Early clinical experience with implantations in humans has shown its safety and satisfactory early results.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Future pulmonary valves in the pipeline include the Medtronic Harmony valve with a self‐expanding hourglass design and a recent positive early feasibility study . Other self‐expandable valves such as the Venous p‐valve (Medtech, Shanghai, China) have been successfully implanted . Additionally, the Edwards Altera adaptive prestent device is undergoing feasibility to allow for a right ventricular outflow tract landing zone in preparation for transcatheter pulmonary valve placement.…”
mentioning
confidence: 99%